Signal transduction in the phosphate regulon of Escherichia coli involves phosphotransfer between PhoR and PhoB proteins - Makino, Kozo 546022; Shinagawa, Hideo 546024; Shinagawa, Hideo 546024; Amemura, Mitsuko 546025; Yamada, Masami 546026; Nakata, Atsuo 546027
PSZJBL